Antibacterial effects of lidocaine and saline irrigation on Escherichia coli in superficial surgical wounds - David Ramírez‐Tapia; José A. Ortega‐Salgado; Stephania Rámirez‐Guzmán; Jorge Lopez‐Lopez; Alejandro Rodríguez‐Baéz; Natalia Nuño‐Lámbarri; Eduardo E. Montalvo‐Javé (Animal Models and Experimental Medicine)
Abstract This study evaluated the antibacterial effects of 2% lidocaine and its combination with 0.9% saline solution on Escherichia coli infection in superficial surgical wounds in Wistar rats. The goal was to determine if these treatments could effectively reduce E. coli Colony Forming Units (CFUs) below the critical threshold of 1 × 105. Seventy male Wistar rats were divided into seven groups, each undergoing different interventions to assess the antibacterial efficacy of lidocaine, with outcomes measured through bacterial cultures and CFU quantification. Results demonstrated a Log10 reduction of approximately 0.44 in E. coli CFUs following infiltration with 2% lidocaine. The combined use of 2% lidocaine infiltration and 0.9% saline irrigation resulted in nearly complete suppression of bacterial growth. These findings suggest that these simple interventions could be valuable in emergency surgical settings to mitigate the risk of surgical site infections and serve as effective prophylactic measures.